ACUTE LEUKEMIA PRESENTING AS ACUTE PANCREATITIS - JATCHAVALA, Janjira; PEKANAN, Patchrin (The ASEAN Journal of Radiology, 2023)
A pediatric patient presented with acute pancreatitis, was found to have acute leukemia. Leukemic nodules was shown in the liver and kidneys by CT scan. The pancreas was diffusely enlarged and had low density which suggested acute inflammatory process and leukemic deposition was likely the cause of pancreatitis. Acute leukemia should be in a differential diagnosis of the pediatric patients who present with acute pancreatitis.